Mastering the information literacy skills in enhancing undergraduate students’ learning process / Wan Nor Haliza Wan Mokhtar … [et al.] - Wan Mokhtar, Wan Nor Haliza; Hussin, Norhayati; Shaifuddin, Norshila; Wan Mohd Saman, Wan Satirah (Universiti Teknologi MARA, 2020)
This study is to identify information literacy skills in enhancing the learning process among undergraduate students. Various kinds of information sources available these days for the students to choose in fulfilling their information needs. In searching for related and relevant information, the undergraduate students are required to have some skills to ensure that they are referring to the right source of information. Information literacy skills are very much needed to be obtained by the searchers in enhancing their learning process. The deliverance of information literacy instruction to students is becoming progressively more significant due to the proliferation of electronic resources and the increased usage of the net as an information source. Information literacy is a set of abilities requiring individuals to recognize when information is needed and have the ability to locate, evaluate, and use the required information effectively. Information literacy has also become more and more significant in the contemporary environment of rapid technological change and proliferating information resources. Because of the escalating complexity of this environment, individuals are faced with diverse, abundant information choices: in their academic studies: in the workplace, and in their personal lives. Information is available throughout the libraries, community resources, special interest organizations, media, and the internet. The objectives of this research are first, to identify the characteristics of information literacy skills in enhancing the learning process among undergraduate students and to examine the relationship between information literacy skills and learning process among undergraduate students. The study involves a descriptive survey research design. A quantitative approach was employed in both data collection and data analysis. The study population is made up of undergraduate students of the Universiti Teknologi MARA (UiTM) Selangor